REFERENCE VALUES FOR HEAVY METALS IN SOILS OF A BASIN IN THE COASTAL ZONE OF NORTHEAST BRAZIL - Marcus Metri Correa; Gilderlaine Souza de Lima; Douglas Monteiro Cavalcante; Fernando Cartaxo Rolim Neto; Rebeca Carolina de Albuquerque Oliveira Lancha (Mix Sustentável)
The presence of heavy metals in the soil poses a threat to both ecosystems and human health. In order to assess the effects of human activities on soil contamination, the environmental monitoring authorities need reference parameters for these contaminants. These parameters, known as Quality Reference Values (QRVs), indicate the natural concentrations of heavy metals in soils unaffected by human interventions and should be established as essential guidelines. Although there are already studies on QRVs in Brazil, the lithological variability justifies the need for more detailed approaches. The objective of this study was to establish QRVs for Al, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn in the soils of the Jaboatão River basin, state of Pernambuco, Brazil. The results revealed that the metals Cr, Cu, and Ni contained some undetected data. The QRV values (mg kg-1) were: 0.43 for Cd, 6.76 for Co, 5.41 for Mn, 21.23 for Pb, and 152.17 for Zn. The values for Co, Pb, and Zn exceeded the QRVs for Pernambuco, established by the State Environmental Agency (CPRH), but did not surpass the Prevention Values set by national legislation.